THE EFFECT OF A HIGHER EDUCATION ON THE HUMAN CAPITAL QUALITY - Patimah, Siti (UIN Ar-Raniry, 2014)
Higher education has a very strategic position toÃ‚Â determine the quality of human capital. Therefore, a higherÃ‚Â education must always strive to provide quality assuranceÃ‚Â services to the interested parties. The more quality customerÃ‚Â service is given, the more college customer will satiesfied thatÃ‚Â have an impact on the increasing investment of the humanÃ‚Â resources (Human Capital).Keywords: Higher Education, Human Capital